Comparative Gross Anatomy of Heart and Lungs in Bewick Swan (Cygnus columbianus) Domestic fowl (Gallus domesticus) and Duck (Anas Platyrhynchous domesticus) - Firdous Ahmad (Indian Journal of Veterinary Anatomy, 2022)
This investigation was carried out to provide a comparative anatomical picture of the Heart and Lungs in Bewick Swan, domestic fowl and in duck. There is very least literature regarding comparative descriptive variations of the heart and lungs in flying and non-flying birds that could adapt various functions, such as flying and running. This study may be used as the basis of a functional study of avian respiratory and circulatory systems.